The orphan's tale [large type] - Jenoff, Pam (Thorndike Press, 2017)
"Sixteen-year-old Noa has been cast out in disgrace after becoming pregnant by a Nazi soldier and being forced to give up her baby. She lives above a small rail station, which she cleans in order to earn her keep. When Noa discovers a boxcar containing dozens of Jewish infants bound for a concentration camp, she is reminded of the child that was taken from her. And in a moment that will change the course of her life, she snatches one of the babies and flees into the snowy night. Noa finds refuge with a German circus, but she must learn the flying trapeze act so she can blend in undetected, spurning the resentment of the lead aerialist, Astrid. At first rivals, Noa and Astrid soon forge a powerful bond. But as the facade that protects them proves increasingly tenuous, Noa and Astrid must decide whether their friendship is enough to save one another--or if the secrets that burn between them will destroy everything."--Amazon.com